Light-driven phenotypic plasticity in the depth-generalist coral, Pavona varians - Claire J. Lewis; Shayle B. Matsuda; Tayler L. Sale; Caitlyn Genovese; Chelsea S. Wolke; Norton Chan; Stephen Ranson; Jake M. Ferguson; Amy L. Moran; David A. Gulko; Peter B. Marko (PLoS ONE, 2025)
Climate change is causing shifts in the spatial distribution of species and a reshuffling of the composition of multiple community types. On coral reefs, deep water can act as both refuges and refugia for corals from the combined negative effects of heat and light stress. Phenotypically plastic generalists that can tolerate both low and high light environments could be disproportionately important on future reefs, persisting in refugia and colonizing vacant shallow reefs. We performed a common garden experiment to investigate the effect of light on three different wild-collected genotypes of the abundant, depth-generalist coral Pavona varians. We measured the growth response and reaction norms of six other morphological and functional traits in full sunlight, 75%, and 90% shade. We also modeled the combined effects of light and temperature on growth. P. varians had positive growth in all three treatments, but increased both skeletal mass and 2-D colony footprint most in 90% shade, with a higher density of corallites, and a less rugose skeleton that may enhance light capture. Areas of the colony corresponding to new growth had greater fluorescence of Symbiodiniaceae communities in the darkest treatment. Light did not alter the functional lipid ratio, nor did communities of Symbiodiniaceae vary with light treatments. The model revealed additively negative, but not synergistic, effects of light and temperature on growth. This additively negative relationship in the model is consistent with the hypothesis that reductions in bleaching at depth could be the product of reduced light stress at depth rather than reduced temperature stress. Light-associated plasticity likely allows P.varians to live in a wide variety of habitats and across a broad depth gradient. In reduced light conditions, this species may mitigate some of the negative effects of bleaching temperatures on growth. We predict that P. varians is likely one of a minority of species that may benefit from deep reef refugia.